2018
DOI: 10.1002/ajim.22923
|View full text |Cite
|
Sign up to set email alerts
|

Impact of California's safe patient handling legislation on musculoskeletal injury prevention among nurses

Abstract: Background This study evaluated the impact of California's safe patient handling (SPH) legislation on musculoskeletal injury prevention among hospital nurses. Methods Two serial cross‐sectional surveys were conducted using postal and online questionnaires in statewide random samples of California registered nurses in 2013 and 2016. Analysis included hospital nurses who performed patient handling (n = 254 and n = 281, respectively). Results In 2016, there were significant improvements in nurses’ knowledge of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…For example, research by Zhang et al found a prevalence of 47.4% in nurses [32]. In this respect, many prevention programs have been implemented in the US a long time ago to prevent and reduce MSDs in nurses [33]. In addition, the conditions and working environment of nurses in the US are also better than in Vietnam [34], which can limit the exposure to hazards in the nurse's working environment.…”
Section: Prevalence Of Ms In Various Anatomicalmentioning
confidence: 99%
“…For example, research by Zhang et al found a prevalence of 47.4% in nurses [32]. In this respect, many prevention programs have been implemented in the US a long time ago to prevent and reduce MSDs in nurses [33]. In addition, the conditions and working environment of nurses in the US are also better than in Vietnam [34], which can limit the exposure to hazards in the nurse's working environment.…”
Section: Prevalence Of Ms In Various Anatomicalmentioning
confidence: 99%
“…As expected, our study participants reported increased provision of lift equipment and more frequent and regular training on SPH since the passage of the SPH law. A recent study of California nurses found statistically significant improvements in hospital SPH programs from 2013 to 2016 with some gaps; in 2016, 87% of hospital nurses with patient handling duties were aware of their hospital’s SPH policy, 66% reported having an SPH committee in their hospital, 80% had lift equipment on their units, and 73% received an SPH training in the previous year (Lee et al, 2018). This focus group study provides further evidence that additional changes may be necessary; for example, participants indicated the need for more nursing staff’s input in the safety committee and more effective training to ensure competency in operating lift equipment among staff across all shifts.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study assessed the impact of the California SPH legislation by comparing data from two surveys conducted in 2013 and 2016 involving California registered nurses (Lee et al, 2018). The study reported significant improvements in nurses’ awareness of their hospital’s policy on SPH, receipt of annual SPH training, and availability of lift equipment, along with significant reductions in the prevalence of work-related musculoskeletal symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, decision algorithms based on a patient's level of mobility, ability to cooperate, weight, and type of transfer are included in SPH recommendations for nursing homes . Research suggests that SPH guidelines are effective in reducing MSD when handling patients . However, there is some concern that SPH practices associated with decreasing back pain, may contribute to shoulder injuries …”
Section: Preventing Msdmentioning
confidence: 99%
“…10 Research suggests that SPH guidelines are effective in reducing MSD when handling patients. [12][13][14][15][16] However, there is some concern that SPH practices associated with decreasing back pain, may contribute to shoulder injuries. 1…”
mentioning
confidence: 99%